Likuiditas, Profitabilitas dan Struktur Modal Terhadap Nilai Perusahaan dengan Variabel Moderasi CSR - Hannawanti Hannawanti; Eduard Ary Binsar Naibaho (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
Corporate value is the main goal of every company. This study examines the relationship of liquidity, profitability, and capital structure to firm value and uses Corporate Social Responsibility as a moderating variable. Liquidity was measured using the Current Ratio, profitability was measured using Return On Assets, capital structure was measured using the Debt to Equity Ratio, firm value was measured using Tobin’s Q and CSR using the G4 version of the CSR Global Reporting Initiative indicator. The observation data in this study were 240 data from non-primary consumer companies listed on the Indonesia Stock Exchange in 2010-2019. This study uses secondary data from S&P Capital IQ and company financial statements. The results of this study indicate that liquidity has a positive direction but has no significant effect on firm value, profitability has a positive direction and has a significant effect on firm value, capital structure has a negative direction but has a significant effect on firm value, CSR as a moderating variable weakens the negative relationship between liquidity and firm value. firm value, CSR as a moderating variable weakens the positive relationship between profitability and firm value, and CSR as a moderating variable strengthens the positive relationship between capital structure and firm value